LC-MS/MS method for the quantitation of decitabine and venetoclax in rat plasma after SPE: Application to pharmacokinetic study - Abdulaziz I. Alnasser; Mohamed M. Hefnawy; Abdullah M. Al-Hossaini; Yousef A. Bin Jardan; Adel S. El-Azab; Alaa M. Abdel-Aziz; Abdulrahman M. Al-Obaid; Ibrahim A. Al-Suwaidan; Mohamed W. Attwa; Manal A. El-Gendy (Elsevier, 2023)
This study developed a novel, sensitive and selective LC-MS/MS method for the concurrent determination of DCB and VTX in rat plasma using encorafenib as internal standard (IS). To identify DCB, VTX, and IS, the positive multiple reaction monitoring (MRM) mode was used. Chromatographic separation was carried out using a reversed-phase Agilent Eclipse plus C18 column (100 mm × 2.1 mm, 3.5 µm) and an isocratic mobile phase made up of water with 0.1% formic acid and acetonitrile (50:50, v/v, pH 3.2) at a flow rate of 0.30 mL/min for 3.0 min. Prior to analysis, the DCB and VTX with the IS were extracted from plasma using the solid-phase extraction (SPE) method. High recovery rates for DCB, VTX and IS were achieved using the C18 cartridge without interference from plasma endogenous. The developed method was validated as per the FDA guidelines over a linear concentration range in rat plasma from 5-3000 and 5-1000 ng/mL for DCB and VTX, respectively with r2 ≥ 0.998. For both drugs, the lower limits of detection (LLOD) were 2.0 ng/mL. After the HLOQ sample was injected, less than 20% of the LLOQ of DCB, VTX, and less than 5% of the IS carry-over in the blank sample was attained. The overall recoveries of DCB and VTX from rat plasma were in the range of 90.68-97.56%, and the mean RSD of accuracy and precision results was ≤6.84%. For the first time, the newly developed approach was effectively used in a pharmacokinetic study on the simultaneous oral administration of DCB and VTX in rats that received 15.0 mg/kg of DCB and 100.0 mg/kg of VTX.